2019
DOI: 10.1097/md.0000000000015946
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the polymorphism rs1800469 of transforming growth factor β in the development of myocardial infarction: meta-analysis of 5460 cases and 8413 controls (MOOSE-compliant article)

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 34 publications
1
3
0
2
Order By: Relevance
“…In the present study, the minor allele of TGFB1 rs1800469 was associated with an increased risk of incident coronary events (HR = 1.30; CI 95% 1.02-1.65; p 0.04), supporting findings from a recent meta-analysis that evaluated associations between rs1800496 and myocardial infarction (MI), identifying significant associations between homozygous and heterozygous minor allele genotypes and increased MI risk, compared to major allele homozygotes [58]. In contrast, a smaller NI case-control study comprising 563 cases and 629 controls, found no association between rs1800496 and MI [24].…”
Section: Plos Onesupporting
confidence: 87%
“…In the present study, the minor allele of TGFB1 rs1800469 was associated with an increased risk of incident coronary events (HR = 1.30; CI 95% 1.02-1.65; p 0.04), supporting findings from a recent meta-analysis that evaluated associations between rs1800496 and myocardial infarction (MI), identifying significant associations between homozygous and heterozygous minor allele genotypes and increased MI risk, compared to major allele homozygotes [58]. In contrast, a smaller NI case-control study comprising 563 cases and 629 controls, found no association between rs1800496 and MI [24].…”
Section: Plos Onesupporting
confidence: 87%
“…The -509C/T functional promoter polymorphism (rs1800469) within the TGFB1 gene has been extensively assessed in different genetic epidemiological studies. Moreover, a number of studies have attempted to investigate whether the polymorphic variants in TGFB1 change TGF β 1 expression [ 19 21 ]. Another genetic polymorphism widely explored in different conditions is rs4803455 involving a C-to-A transition, which is located in intron 2 of TGFB1 and was therefore selected in our study.…”
Section: Discussionmentioning
confidence: 99%
“…They combine the results of single-gene association studies, providing an excellent opportunity to observe the role of a single genetic variation in a more heterogeneous and larger population. Over the past 10-15 years, meta-analyses have looked at a wide range of conditions associated with heart disease, including CAD itself [23][24][25][26]. Unfortunately, meta-analyses, like GWAS, can be biased by population stratification, variability in control group selection, different study approaches, or different scales of biochemical values.…”
Section: Role Of Single-nucleotide Polymorphisms In Cadmentioning
confidence: 99%